Fatal Penetrating Lacerated Wound By Tusk of Indian Wild Boar - Akhade, S P; Rohi, K R; Phad, L P; Dixit , P G (Journal of Indian Academy of Forensic Medicine, 2015)
Attack of wild boar is rare and death by single injury on body due to attack of wild boar is rarest of rare. Although wild boars do not generally pose a threat to people, they occasionally attack humans. Due to the clearing of natural boar habitats, the number of interactions, including aggressive ones, between humans and boars has increased. When dealing aggressively with a human, boar will charge at them. When ramming into a person, the boar will slash the tusks upwards, creating sizeable open lacerations on the skin. Due to the height of the boar relative to a human, most wounds are inflicted to the upper legs, fatalities do occasionally occur. Wild boar attacks are under reported. There are very few cases of human attack by wild boars mentioned in literature. This case is reported for single fatal penetrating lacerated injury to lower limb inflicted by tusk of wild boar.